The use of THRIVE in otolaryngology: our experiences in two Australian tertiary facilities - Lau, Joshua; Loizou, Peter; Riffat, Faruque; Stokan, Murray; Palme, Carsten E. (Australian Journal of Otolaryngology; Vol 2 (August 2019): Australian Journal of Otolaryngology, 2019)
Whilst high-flow nasal oxygen has had a well-established use in critical care units, it has only recently been trialled as a method for pre-oxygenation. This novel technique, known as Transnasal Humidified Rapid-Insufflation Ventilatory Exchange (THRIVE), utilizes apnoeic oxygenation to extend the apnoeic window and allow for a smoother intubation, especially in difficult airways. Results have been promising, with apnoeic windows of up to 65 min attainable without desaturation below 90%. Although THRIVE has not yet seen extensive use outside of this setting, it has begun to be trialled as a sole method of ventilation in phonolaryngeal procedures. We report our experiences, since the start of 2017, with using THRIVE as the sole mode of ventilation in various otolaryngological procedures, including rigid laryngoscopies, endoscopic tracheo-bronchoscopies and transoral laser microsurgery. Twenty-eight cases from two tertiary facilities (Westmead Public/Private Hospitals & Chris O’Brien Lifehouse) were retrospectively reviewed where THRIVE had been trialled as the sole method of ventilation with the support of an experienced anaesthetist (Murray Stokan). We have found THRIVE to be successful in maintaining adequate oxygenation whilst providing sufficient apnoeic windows to perform phonolaryngeal procedures. It allows for an improved field of view to facilitate thorough hypopharyngeal/laryngeal inspection & biopsy. In our cases incorporating the CO2 laser, we report no intra/post-operative complications. THRIVE is a safe, effective and well-tolerated airway technique that warrants further trialling in otolaryngological surgery.